A re-examination of the empirical performance of the Longstaff and Schwartz two-factor term structure model using real yield data. (August 2013) - Faff, Robert; Treepongkaruna, Sirimon
In this study, we apply the Longstaff and Schwartz (1992) two-factor term structure model to real yields across eight countries. As such, we improve on many prior studies that have inappropriately tested this formulation using nominal yield data. We use the generalized method of moments to test the cross-sectional restrictions imposed by the Longstaff and Schwartz model, as well as the Cox–Ingersoll–Ross one-factor model. Further, we compare the forecasting ability from both models. Our findings support the superiority of the two-factor model. We confirm general reliability of prior research in this area, despite the unfortunate reliance on nominal data in such earlier tests.